Pengaruh Viral Marketing, Desain Produk Melalui Citra Merek sebagai Variable Intervening terhadap Minat Beli Sepatu Aerostreet : Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya - Kania Rifdah Gunawan; Hadita Hadita; Neng Siti Komariah; Dewi Puspaningtyas Faeni; Yayan Hendayana (International Forum of Researchers and Lecturers, 2024)
This research aims to find out whether Brand Image can influence Viral Marketing and Product Design on Purchase Intention in Aerostreet Shoes products at the Faculty of Economics and Business, Bhayangkara University, Greater Jakarta. The method used in this research is a quantitative method. The sample used was 170 respondents and focused on students at the Faculty of Economics and Business, Bhayangkara University, Jakarta Raya. The sampling technique uses Purposive Sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use statistical methods with SmartPLS 4.0 software. The results of this research show that there are variables that influence each other, as in the following brief explanation: 1). Viral Marketing has a positive and significant effect on Purchase Intention, 2). Product Design has a positive and significant effect on Purchase Intention, 3). Viral Marketing has a positive and significant effect on Brand Image, 4). Product Design has a positive and significant effect on Brand Image, 5). Brand Image has a positive and significant effect on Purchase Intention, 6). Brand Image is able to fully mediate Viral Marketing on Purchase Intention, 7). Brand Image is able to fully mediate Product Design on Purchase Intention.